The Little Data Book on Africa 2007 - World Bank (Africa Development Indicators, 2007)
This book provides profiles of over 50 countries with 54 development indicators about people, environment, economy, technology, infrastructure, trade and finance, all in one handy, pocketsized volume. A must have for anyone interested in today's development challenges in subSaharan Africa